2017
DOI: 10.3766/jaaa.16075
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Gaps-In-Noise Test as an Index of the Enhanced Left Temporal Cortical Thinning Associated with the Transition between Mild Cognitive Impairment and Alzheimer’s Disease

Abstract: The results support central auditory processing evaluation in the elderly population as a promising tool to achieve earlier diagnosis of dementia, while identifying central auditory processing deficits that can contribute to communication deficits in the MCI patient population. A measure of temporal resolution (GIN) may offer an early, albeit indirect, measure reflecting left temporal cortical thinning associated with the transition between MCI and Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 57 publications
1
33
0
1
Order By: Relevance
“…Rather, there appear to be specific impairments of auditory perception which precede full-blown Alzheimer's disease (Gates et al, 2002; Swords et al, 2018). One such deficit shown by adults with Mild Cognitive Impairment (MCI) is a deficit in detecting gaps in background noise (Iliadou et al, 2017). Gap detection is a measure of temporal acuity that is correlated with speech perception deficits in older adults (Glasberg et al, 1987; Fitzgibbons and Gordon-Salant, 1996; Snell and Frisina, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, there appear to be specific impairments of auditory perception which precede full-blown Alzheimer's disease (Gates et al, 2002; Swords et al, 2018). One such deficit shown by adults with Mild Cognitive Impairment (MCI) is a deficit in detecting gaps in background noise (Iliadou et al, 2017). Gap detection is a measure of temporal acuity that is correlated with speech perception deficits in older adults (Glasberg et al, 1987; Fitzgibbons and Gordon-Salant, 1996; Snell and Frisina, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Because speech segmentation and phoneme identification depend on gaps and other temporal cues in speech sounds, gap detection serves as a model for speech processing. Because patients show a gap detection deficit early, in the MCI phase, this measure has been proposed as a biomarker that could achieve earlier diagnosis of dementia (Iliadou et al, 2017). Although not all MCI patients go on to develop Alzheimer's, longitudinal studies have shown that deficits in central auditory processing (such as dichotic listening) can predict the subsequent development of Alzheimer's disease with a relative risk ratio of up to 23 (Gates et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Iliadou et al also reported the results of evaluating auditory perception in a group of older adults diagnosed with mild cognitive impairment. Auditory perception was evaluated by assessing temporal resolution in the Gaps-In-Noise test, and suggested that central auditory processing evaluation in the elderly population should be a promising indicator to achieve earlier diagnosis of dementia [27]. Swords et al reviewed the literature concerning auditory dysfunction in Alzheimer's disease and concluded that a dichotic listening task showed high diagnostic and prognostic significance in persons with Alzheimer's disease; therefore, audiological approaches are a low-cost way to identify an early window of Alzheimer's disease pathology [28].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, performance deficits on cognitive measures such as STM would not be an adequate explanation for the source of disparate disorders, such as language impairments, dyslexia, dyscalculia, ADHD, learning problems, or cognitive difficulties seen in autism. Moreover, correlation between APD and cognition does not impute a specific causal direction ( 33 ). It is essential that in the papers where APD is diagnosed and not just suspected, IQ cannot explain auditory processing deficits ( 15 , 34 ).…”
Section: Misconception 4: Apd Reflects Cognitive Deficitsmentioning
confidence: 99%